(untitled) (Archaeologia Adriatica, 2022)
In 1960, the Archaeological Museum in Zadar, led by Šime Batović, conducted archaeological excavations of the Jaruv hill fort and eight tumuli in Dobropoljci. Since the research is known only through a short report, the authors on this occasion publish the remaining research documentation, which is kept in the museum, and, on the basis of this research, correct certain interpretations, at the same time giving the broader context of these findings based on recent discoveries about burials.